ENDOTHELIAL MICROPARTICLES: COMPLEX STRUCTURES THAT HAVE POTENTIAL TO ATTENUATE OSTEOGENIC DIFFERENTIATION OF HUMAN SMOOTH MUSCLE CELLS. (21st November 2014) - Moreno-Martinez, D; Wilkinson, FL; Parker, B; Pieri, M; Barraclough, M; Bruce, I; Alexander, MY
Abstract : Endothelial microparticles (EMPs) are complex structures with pleiotropic properties and are emerging as an index of endothelial damage. We demonstrate their levels can be modulated by anti-inflammatory treatment and their existence in the circulation raises the question about their physiological role. Our studies aim to investigate the molecular components of EMPs, and whether EMPs modulate matrix mineralisation. Flow cytometry was used to quantify circulating EMPs (AnnexinV+/CD31+/CD42b−) in lupus patients, pre- and post- anti-inflammatory treatment. EMPs were generated in vitro using TNF-activation of human aortic endothelial cells and used for proteomic analysis and to treat human vascular smooth muscle cells (HVSMC). Alizarin Red staining was used to quantify levels of mineralisation using an in vitro model of calcification. We show that EMP levels are significantly elevated in lupus patients compared to healthy subjects (p<0.05) and are reduced following anti-inflammatory treatment. Among proteins identified within EMPs from a proteomic screen was PTX3, a member of the pentraxin family that has been shown to reflect a cardiovascular protective effect potentially linked with its capacity to control inflammation. Alizarin Red staining demonstrates an attenuation of mineralisation in EMP-treated HVSMCs compared to untreated cells cultured in osteogenic media in vitro (p<0.05). We conclude that EMPs may prevent the reprogramming of SMCs to an osteogenic pathway in vitro, which may be, in part linked with PTX3. Further studies are required to determine how MPs contribute to pathophysiological mechanisms in vivo and whether the circulating property of MPs may represent a new biomarker in vascular calcification.